Contributions to the knowledge of the genus Plantago (Plantaginaceae) in the Central-West region of Brazil - Hassemer, Gustavo (Phytotaxa, 2017)
Here, I present contributions to the knowledge of the genus Plantago (Plantaginaceae) in the Central-West region of Brazil, including the first records of P. australis (more specifically: P. australis subsp. hirtella), P. commersoniana and P. napiformis in this Brazilian region, and the first records of P. major in Mato Grosso state. I also typify here the name P. hirtella, which is the basionym of P. australis subsp. hirtella, and also its heterotypic synonyms P. galeottiana, P. leptophylla, P. schiedeana and P. veratrifolia. Furthermore, I provide an identification key to the five species of Plantago recorded in the Central-West region of Brazil.